A Comparison between Discounted Cash Flow and Residual Earning Models for Use in Equity Valuation - Niu, Jie (2005)
This paper mainly tries to answer three questions by comparing the discounted cash flow model (DCF) and residual earning model (REM). Firstly, which model will perform better in the valuation of equity? Secondly, how about the robustness of the different model? That is, will they give the same result under different assumptions, such as growth rates, evaluation horizons? Thirdly, which model has better explainability on the share price of traded firms? The empirical research result indicates that REM will perform better in terms of accuracy, reliability, robustness and explainability than DCF with shorter valuation horizon. However, when valuation horizon become longer, the situation reversed.